Intrinsic Motivation as Mediation Between Organizational Justice and Organizational Citizenship Behavior (Study on Employees of PDAM Tirta Anom, Banjar City) - Adi Muhammad Nur Ihsan (Syntax Corporation Indonesia, 2023)
The purpose of this research is to determine the influence of procedural justice, interactional justice, and intrinsic motivation on Organizational Citizenship Behavior (OCB). The respondents in this study are employees of PDAM Tirta Anom Kota Banjar. The number of respondents in this study was determined using the Slovin method, and a total of 73 respondents were included. Based on the research findings and data analysis using multiple regression, the following conclusions can be drawn: (1) procedural justice does not have an effect on intrinsic motivation, (2) interactional justice does not have an effect on intrinsic motivation, (3) procedural justice has a positive effect on OCB, (4) interactional justice does not have an effect on OCB, (5) intrinsic motivation does not mediate the relationship between procedural justice and OCB, (6) intrinsic motivation does not mediate the relationship between interactional justice and OCB. Considering these results, there is a need for improvement in treating employees fairly. This fairness can be in the form of both procedural and interactional justice. This will enhance employees' perception of fairness and encourage positive behavior. Additionally, the company should create a conducive work environment, including favorable working conditions and mutual support among employees, in order to enhance positive employee behavior that supports the company's performance.